Central Serous Chorioretinopathy Associated with Corticosteroid Use in a Patient with Leber Hereditary Optic Neuropathy: A Case Report - Lepsa Zoric; Aleksandra Petrovic; Vladimir Milutinovic (Medicina)
Introduction. Leber hereditary optic neuropathy (LHON) is a condition characterized by bilateral acute or subacute vision loss in seemingly healthy individuals. Depending on the disease stage and initial presentation, it is often diagnosed as optic neuritis. Elevated levels of endogenous and exogenous glucocorticoids have been associated with the onset of central serous chorioretinopathy (CSCR). In our patient, CSCR developed after only three days of pulse corticosteroid therapy, prescribed due to initial presentation as bilateral optic neuritis (papillitis). Objective. Through our case report, we aimed to highlight that CSCR can develop after the initiation of pulse corticosteroid therapy in a patient with LHON and to propose choroidal thickness as a potential contributing factor for this complication. Case Presentation. A 27-year-old male patient presented with painless subacute vision loss in both eyes. The decline in vision developed gradually over 20 days, prior to the patient’s referral to the UKCS Eye Disease Clinic for further examination and treatment, and was not accompanied by pain during eye movements. Initial investigations upon admission to the clinic established the diagnosis of optic neuritis. Consequently, pulse corticosteroid therapy was administered. Three days after the initiation of intravenous methylprednisolone, the patient developed bilateral central serous chorioretinopathy. After cessation of therapy, there was a rapid resolution of choroidopathy, but no improvement in visual acuity, prompting genetic testing. Subsequent laboratory results revealed a positive test for the LHON mutation m.3460 G>A (MT-ND1). Conclusions. LHON is often misdiagnosed as optic neuritis, as upon initial presentation the optic nerve disk often does not exhibit the apparent characteristics of LHON. Numerous studies have documented the development of central serous chorioretinopathy following corticosteroid treatment, though none have reported the onset of CSCR after only three days of pulse corticosteroid therapy. Increased choroidal thickness is a characteristic of the acute phase of LHON and may be associated with the development of CSCR in our patient.